The Current Digital Financial Literacy and Financial Behavior in Indonesian Millennial Generation - Rita Rahayu; Syahril Ali; Amalda Aulia; Retnoningrum Hidayah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to investigate the relationship between the level of digital financial literacy (DFL) and financial behaviors, namely saving behavior, spending behavior, and investment behavior among the millennial generation in Indonesia.Design/Methodology/Approach: A survey method was performed in this study, and 741 millennial generations aged 25–40 years from several cities in Indonesia participated in this study. The Structural Equation Model using SmartPLS was employed to estimate the relationship of the latent variable.Research findings: Based on the data, it was found that DFL had a positive effect on spending behavior, saving behavior, and investment behavior. In addition, this study also revealed that social factors such as income had a significant influence on the DFL.Theoretical contribution/Originality: This research provides a map of the level of digital financial literacy among the millennial generation in Indonesia. In addition, since there is a limited study related to digital financial literacy, this research contributes to the enrichment of literature, especially related to digital financial literacy.Practitioner/Policy implication: It is expected that this result will be used by policymakers to make a policy regarding digital financial literacy, especially for millennial generations.Research limitation/Implication: Most respondents who participated in this study came from West Sumatra, affecting the generalization of the research results.